Medical image analysis of knee images for sarcopenia detection using mri - Chitradevi (2014)
Osteoarthritis is a degenerative syndrome with health impairment leads to decrease in their physical activities, inflammation, stiffness and severe pain in the elderly population. It is necessary for us to know about the mechanism behind Progressive loss